Systematic Time-Dependent, Multimode Simulation Study of a Ka-Band, Three-Cavity Second-Harmonic Gyroklystron Amplifier - Swati, M.V.; Jain, P.K. (Institute of Electrical and Electronics Engineers Inc., 2020)
The multimode beam-wave interaction behavior in the RF interaction structure of a second-harmonic, 32.3 GHz gyroklystron amplifier operating in the TE02 mode has been studied by simulating the device using a commercial 3-D particle-in-cell code, 'CST Studio Suite.' The effect of the variation of numerous parameters, such as driver frequency, RF power, magnetic-field strength, and beam current, has been investigated to realize the sensitivity of the device performance to these parameters. The effect of varying the position of the buncher cavity with respect to input and output cavity on the 3 dB gain and efficiency has also been investigated. The simulation results show that the designed gyroklystron amplifier produces a constant RF output power of 315 kW at 32.3 GHz center frequency for a 70 kV, 20 A electron beam. The 3 dB gain of the device is obtained as 26 dB with 22.5% electronic efficiency and 11 MHz bandwidth. The velocity spread is assumed as 0% for the present work. For validation, the simulated results have been compared with the previously reported experimental results and the previously reported analytical results, which are found to be in good agreement (i.e., less than 5% variation). © 1973-2012 IEEE.
Keywords: Beam–wave interaction; gyrodevices; gyroklystron amplifier; millimeter wave; PIC simulation; second harmonic